Helmut Stessl and Sue Stessl interviewed by Alex Hood and Annette Hood in the Alex Hood folklore collection - Stessl, Helmut, 1936-; Stessl, Sue, 1937-; Hood, Alex, 1935-; Hood, Annette, 1948- (2010)
Folkloric recording. Helmut Stessl talks about his parents' backgrounds; the aftermath of WWI; his family's many moves, finally to Austria; his schooling; the loss of school time due to WWII; conditions in Europe at that time; his apprenticeship as a fitter and turner; the move to Australia (1956); being sent to the Migrant Camp at Bonegilla, Vic., absconding; obtaining work as a toolmaker; how work in Tasmania, led to work on the Snowy River Scheme. Sue Stessl talks about how she arrived in Cooma, N.S.W.; her schooling in Sydney doing a shorthand/typing course; how she met Helmut and her working life. Helmut describes work conditions e.g. shift work, contract work, penalty and bonus schemes, taxes and wages; he describes the tunnels and methods of work. Sue talks about the social life; her involvement in musical shows; the problems with lonely men; gambling; prostitution. Helmut discusses deaths and injuries underground; the 'buddy system'; his first days on the Snowy River Scheme; the class and nature of workers, shift work; Cooma in boom times; history of Ski fields, huts and lodges; leaving the area for a job in Sydney and later move to Newcastle; their family. Sue talks about her family background; her father working at Mt. Magnet as a General Practioner (Dr.).
They talk more about the Snowy and Sue City, a company town and work place, its construction and demise; the lack of knowledge of Snowy Scheme today, achievements of scheme. Helmut describes his work in Mt. Isa; the changes in techniques, 'fly in, fly out'; work on the Ord River and American operations. They talk of cultural differences; the loss of expertise after Snowy Scheme. Helmut speaks of old friends; the Snowy Anniversary; Jindabyne; bushfires and aftermath; the removal of cattle from the Snowy; his night work experiences, the wildlife; the loss of life on the Snowy scheme and tragic deaths; occupational and safety methods today.
Recorded on 9 December 2010 in Valentine, N.S.W.
Digital master available
Timed summary (3 p.)
Keywords: Stessl, Helmut, -- 1936- -- Interviews; Stessl, Sue, -- 1937- -- Interviews; Snowy Mountains Hydro-Electric Scheme -- History; World War, 1939-1945 -- Personal narratives; Snowy Mountains Region (N.S.W.) -- History